Constrictive Pericarditis Associated with Atypical Antipsychotics - Kuan-chin Jean Chen; Aashish Goela; Patrick Teefy; L. Ray Guo (Case Reports in Cardiology)
We report the successful surgical intervention in a case of constrictive pericarditis after long-term use of atypical antipsychotics. Pericarditis developed in our patient with a longstanding history of schizophrenia treated with atypical antipsychotics. Pericardiectomy was undertaken, and the patient's presenting symptom of shortness of breath resolved subsequently with an uneventful postoperative course.